Molecular detection of intrauterine microbial colonization in women with endometriosis. (April 2016) - Khan, Khaleque N.; Fujishita, Akira; Masumoto, Hiroshi; Muto, Hideki; Kitajima, Michio; Masuzaki, Hideaki; Kitawaki, Jo
Abstract: Objective: Increased intrauterine microbial colonization by bacteria culture method and occurrence of endometritis have been reported in women with endometriosis. Here we investigated microbial colonization in intrauterine environment and cystic fluid of women with and without endometriosis by molecular approach. Study design: This is a case-controlled biological study with a total of 32 women each with and without endometriosis. Among them, 16 each in these two groups of women received treatment with gonadotropin-releasing hormone agonist (GnRHa). Pattern of microbial colonization in endometrial swabs and endometrioma/non-endometrioma cystic fluid was examined using broad-range polymerase-chain reaction (PCR) amplification of bacteria targeting 16S rRNA gene (rDNA). After quantification of index PCR product, 16S rDNA metagenome sequence analysis was done by Illumina Miseq system. Results: A wide proportion (0.01–97.8%) of multiple bacteria was detected in both endometrial swabs and cystic fluid collected from women with and without endometriosis. 16S metagenome assay indicated that proportion of Lactobacillacae was significantly decreased ( p < 0.01) and of Streptococcaceae, Staphylococaceae, Enterobacteriaceae was significantly increased ( p < 0.05 for each) in GnRHa-treated women with endometriosis than in GnRHa-untreated women. While bacteria culture method failed to detect a single colony, 16S metagenome assay could detect significantly higher percentage of Streptococcaceae ( p < 0.01) and Staphylococaceae ( p < 0.05) in the cystic fluid derived from women with ovarian endometrioma comparing to that in cystic fluid collected from non-endometrioma cysts. Conclusion: These findings indicate the occurrence of sub-clinical infection in intrauterine environment and in the cystic fluid of ovarian endometrioma. Additional side effect of GnRHa treatment in promoting silent intrauterine and/or ovarian infection should be considered.